Tailored Dealloying Products of Cu-based Metallic Glasses in Hydrochloric Acid Solutions - Wang,Zhifeng (2014)
Free dealloying of Cu-Hf-Al metallic glasses in HCl electrolytes are studied in this paper. The results show that the electrolyte concentration and dealloying time strongly influence the type of dealloying products. A superficial dealloying happens in diluted HCl electrolytes while a complete dealloying occurs in concentrated HCl electrolytes. The results present that Cu2O microparticles with regular morphology can be tailored on glassy surfaces in 0. 05 M HCl solution by controlling the dealloying time. Furthermore, the designable products of nanoporous Cu, Cu2O nanoplates and CuO microwires can be fabricated in 1. 2 M HCl electrolyte with the dealloying time. Due to a big difference of examined Cu-Hf-Al alloys in the electrolyte concentration and dealloying time, one or mixed dealloying products (Cu, Cu2O and CuO), which depend on the progress of relative chemical reactions and the different dealloying route, will finally be produced.